Bugis Migration Various Continues and Success - Rahmawati Harisa (Journal of Research and Multidisciplinary, 2020)
This article discusses the migration process of the Bugis people in various regions. To reach a bright spot in this study, the authors use historical, sociological, anthropological studies, and writings supporting this paper to complete the desired information. This study's results revealed that the Bugis people's desire to migrate because of the real situation that allows them to migrate. This can be seen at least in two ways, namely the sociological reality and psychological reality. Sociological Realityin In the middle of Islamization's process related to the Gowa Kingdom Political movement to subdue the kingdoms that did not yet embrace Islam. Psychological reality because of the chaos that was allegedly hurting his survival. Population movements carried out by Bugis communities in various regions turned out to be able to provide a positive impact on their migration. The most scientific thing to provide evidence of the Bugis migrating community's success is to look at the highest position held in the area of ​​migration. They can also form their ethnicity without changing or hurting the culture that already exists in each region where they migrate.